How to Fight Deflation in a Liquidity Trap : Committing to Being Irresponsible - Eggertsson, Gauti (IMF Working Papers; Working Paper ;, 2003)
I model deflation, at zero nominal interest rate, in a microfounded general equilibrium model. I show that deflation can be analyzed as a credibility problem if the government has only one policy instrument, money supply carried out by means of open market operations in short-term bonds, and cannot commit to future policies. I propose several policies to solve the credibility problem. They involve printing money or nominal debt and either (1) cutting taxes, (2) buying real assets such as stocks, or (3) purchasing foreign exchange. The government credibly "commits to being irresponsible" by using these policy instruments. It commits to higher money supply in the future so that the private sector expects inflation instead of deflation. This is optimal, since it curbs deflation and increases output by lowering the real rate of return.